Origins and Implications of Family Structure across Italian Provinces in Historical Perspective - Graziella Bertocchi; Monica Bozzano (Institute for the Study of Labor (IZA), 2016)
In this study we review the literature on the origins and implications of family structure in historical perspective with a focus on Italian provinces. Furthermore we present newly-collected data on three of the main features of family structure: female mean age at marriage, the female celibacy rate, and the fraction of illegitimate births. The data are collected at the provincial level for 1871, the year of Italy's political unification. The analysis of the data allows us to confirm and quantify the geographic differentiation in family patterns across the country. We also illustrate the links between family structure and a set of socio-economic outcomes, in the short, medium, and long run.
Keywords: J12; N33; O1; Z1; 330; family structure; Italian provinces; institutions; culture; development